Sediment Bulk Density Effects on Benthic Macrofauna Burrowing and Bioturbation Behavior - Wiesebron, Lauren E.; Steiner, Natalie; Morys, Claudia; Ysebaert, Tom; Bouma, Tjeerd J. (Frontiers in Marine Science, 2021)
Benthic macrofauna are a key component of intertidal ecosystems. Their mobility and behavior determine processes like nutrient cycling and the biogeomorphic development of intertidal flats. Many physical drivers of benthic macrofauna behavior, such as sediment grain size, have been well-studied. However, little is known about how sediment bulk density (a measure of sediment compaction and water content) affects this behavior. We investigated the effect of bulk density on the burrowing rate, burrowing depth, bioturbation activity, and oxygen consumption of bivalves (Limecola balthica, Scrobicularia plana, and Cerastoderma edule) and polychaetes (Hediste diversicolor and Arenicola marina) during a 29-day mesocosm experiment. We compared four sediment treatments consisting of two sediments of differing grain size classes (sandy and muddy) with two bulk densities (compact and soft). Overall, bulk density had a strong effect on benthic macrofauna behavior. Benthic macrofauna burrowed faster and bioturbation more intensely in soft sediments with low bulk density, regardless of grain size. In addition, L. balthica burrowed deeper in low bulk density sediment. Finally, we found that larger bivalves (both C. edule and S. plana) burrowed slower in compact sediment than smaller ones. This study shows that benthic macrofauna change their behavior in subtle but important ways under different sediment bulk densities which could affect animal-sediment interactions and tidal flat biogeomorphology. We conclude that lower bulk density conditions lead to more active macrofaunal movement and sediment reworking.